English Teachers’ Instructional Communication in Implementing Finnish-Based Innovative Learning: A Case Study - Alma Ferbyana; Deddy Mulyana; Hadi Suprapto (Borong Newinera Publisher, 2026)
Instructional communication plays a central role in shaping meaningful learning experiences, particularly within student-centered and dialogical educational paradigms. This study aims to explore the forms and implementation of instructional communication in English learning based on the Finnish educational approach at Mutiara Insani Junior High School, Purwakarta. Employing a qualitative case study design, the research focuses on English teachers and eighth-grade students as the main subjects. Data were collected through classroom observations, in-depth semi-structured interviews, and document analysis, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing with triangulation to ensure credibility. The findings reveal that instructional communication in English learning is implemented in multimodal and contextual forms, including verbal-bilingual communication, nonverbal communication, media-supported communication, hands-on activities, collaborative interaction, and affective communication. Teachers position themselves as facilitators who encourage dialogue, provide constructive feedback, and create a psychologically safe learning environment. The integration of Finnish-based learning principles emphasizes student-centeredness, joyful learning, contextual relevance, and minimal exam orientation. Supporting factors include positive teacher–student relationships, flexible teaching strategies, and the use of varied media, while inhibiting factors involve differences in student proficiency, emotional readiness, time limitations, and vocabulary constraints.